2021
DOI: 10.1136/jitc-2021-002523
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and immunological evaluation of self-assembled antigenic peptides from dual-antigen targets: a broad-spectrum candidate for an effective antibreast cancer therapy

Abstract: BackgroundConsidering the narrow immune response spectrum of a single epitope, and the nanoparticles (NPs) as a novel adjuvant can achieve efficient delivery of antigenic peptides safely, a nano-system (denoted as DSPE-PEG-Man@EM-NPs) based on cathepsin B-responsive antigenic peptides was designed and synthesized.MethodsHighly affinitive antigenic peptides were delivered by self-assembled NPs, and targeted erythrocyte membranes acted as a peptide carrier to improve antigenic peptides presentation and to streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The experiment was carried out according to the instructions of the CytoTox 96 ® Non-Radioactive Cytotoxicity Assay (Promega). The cell killing rate was calculated accordingly [30].…”
Section: Cd8 + T Cells Activation and In Vitro Killing Effectmentioning
confidence: 99%
“…The experiment was carried out according to the instructions of the CytoTox 96 ® Non-Radioactive Cytotoxicity Assay (Promega). The cell killing rate was calculated accordingly [30].…”
Section: Cd8 + T Cells Activation and In Vitro Killing Effectmentioning
confidence: 99%
“…Wei et al. developed a self-assembled peptide system as a novel adjuvant that can efficiently deliver two antigens (MAGE/NY-ESO-1) ( 86 ). The SANPs not only widened the response range within the same molecule but also significantly prolonged the plasma half-life of single antigenic peptides, which can be a broad-spectrum candidate for effective breast cancer therapy.…”
Section: Several Sanps For Vaccine Designmentioning
confidence: 99%
“…Nevertheless, it was found that CD58 and CD59 molecules expressed on erythrocytes membranes could enhance immune recognition and antigen presentation [91]. Shi et al fabricated a modified erythrocytes membrane-cloaked delivery vector (DSPE-PEG-Man@EM-NPs) with shell-core structures for antigen pep-tides delivery towards DCs [39]. The outer layer was an erythrocytes membrane, with DSPE-PEG-mannose decoration that could allow the DC targeting ability, and the inner core was a kind of self-assembly NP, based on amphiphilic cathepsin B-responsive dipeptide to covalently link antigenic peptides MAGE and NY-ESO-1.…”
Section: Erythrocyte-based Drug Delivery Systemsmentioning
confidence: 99%